Need to consider damaging aseismic geodeformations when developing construction technologies - Учитель, Игорь Леонидович; Капочкин, Борис Борисович (Eastern-European Journal of Enterprise Technologies, 2015)
As a result of the research, an attempt to justify the need to consider the risk of destruction of engineering structures by aseismic geodeformations depending on the type of building was made. An increase in the amplitude of the daily amplitudes of earth tidal deformations in the dates when syzygy coincides with zero declination of the Moon and the perihelion of the Moon was chosen as a criterion for selecting the activation period of global-scale geodeformations. The selected criterion corresponds to more than two-fold increase in the amplitude of geodeformations on these dates. As a result, anomalous dynamic and kinematic characteristics of the global geodeformation process in April-May 2013, accompanied by a strong earthquake in the Sea of Okhotsk 05/25/2013 were investigated. Using heterogeneous time series of improbable “resonance” emergencies, composed for the time period of April-May 2013 and including the cases of gas burst, sinkhole collapse, collapse of buildings, underground mines, ditches, rupture of oil and gas pipelines, emergencies, related to bridges and railway accidents, as well as statistical methods, it was shown that the global geodeformation process is statistically associated with different types of emergencies. It was shown that the time series of emergencies does not obey a normal distribution of random variables since it has a statistically significant periodic component. It was found that the frequency features of emergencies in the period under review are consistent with similar frequency features of dynamic factor of geodeformations. In a first approximation, it can be noted that emergencies, associated with sinkhole collapses and lithospheric gas bursts occur most frequently in the geodynamic activity period, deformation processes appear less often directly under the buildings and pipelines. Geodeformations for bridges and railways are the least dangerous.